2012
DOI: 10.1097/prs.0b013e3182365fda
|View full text |Cite
|
Sign up to set email alerts
|

The Feeling of Healing

Abstract: Morgan S. Measurement of carboxyhemoglobin and methemoglobin by pulse oximetry: A human volunteer study. Anesthesiology 2006;105:892-897. 3. Clack SL, Shah N, Hoang TD, Gupta B. A comparison of four major brands of pulse oximeters (PO) with Masimo SET PO during motion and low perfusion under normoxic and hypoxic conditions in human volunteers (Abstract). Anesthesiology 2001;95:A586. 4. Hager H, Dayakar R, Kurz A. Perfusion index: A valuable tool to assess chances in peripheral perfusion caused by sevoflurane? … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
5
0
1
Order By: Relevance
“…Furthermore, during healing wounds are initially hyperinnervated, including itch‐conducting sensory nerves. The nerve density normalizes during scar maturation – it has been observed that tissues fail to heal when there is no nerve supply …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, during healing wounds are initially hyperinnervated, including itch‐conducting sensory nerves. The nerve density normalizes during scar maturation – it has been observed that tissues fail to heal when there is no nerve supply …”
Section: Discussionmentioning
confidence: 99%
“…The nerve density normalizes during scar maturation it has been observed that tissues fail to heal when there is no nerve supply. 7 However, it cannot be excluded that in the different forms of EB, the underlying defect triggers specific reaction 0Á68** 0Á32 0Á87** 100 Consequences (5) 0Á52** 0Á41* 0Á68** 0Á66** 100…”
Section: Discussionmentioning
confidence: 99%
“…56 These, and products of the inflammatory cascades that they initiate, might not only mediate the recruitment of immune cells to the wounded site (Figure 2; box B2), but also directly activate sensory neurons, triggering itch signals or even increasing the neurons' responsiveness to pruritogens (Figure 2; box E). 21 In turn, sensory fibres in the skin release neuromediators, including substance P, calcitonin gene-related peptide, brain-derived natriuretic peptide and nerve growth factor, 20,57,58 all of which are implicated in pruritus pathophysiology (Figure 2; box F). 18 The concept that the wound healing process triggers pruritus is supported by observations that this is a major problem in patients with burns.…”
Section: Inflammation and Epidermolysis Bullosa Skinmentioning
confidence: 99%
“…For instance, products containing growth factors or cytokines can be applied for accelerating healing and reducing wound scarring as they stimulate the proliferation of many types of skin cells and thus enhance epidermal renewal. 60,64 Centella asiatica extract is a traditional ingredient with well-documented wound-healing properties, as well as multiple other healthcare benefits. The effectiveness of this extract for skin repair has been demonstrated in animal models of wound healing, with the effects most likely being due to the presence of the constituent bioactives, madecassoside and asiaticoside.…”
Section: Healing Treatmentsmentioning
confidence: 99%